Eyetracking during free visual exploration detects neglect more reliably than paper-pencil tests. (August 2020) - Kaufmann, Brigitte C.; Cazzoli, Dario; Pflugshaupt, Tobias; Bohlhalter, Stephan; Vanbellingen, Tim; Müri, René M.; Nef, Tobias; Nyffeler, Thomas
Abstract: Neglect after stroke is most accurately diagnosed by a systematic, ecological observation during everyday behaviour using the Catherine Bergego Scale (CBS). However, the CBS is time-consuming and often omitted in clinical settings, especially stroke units. In this study, we aimed to explore if video-oculography during free visual exploration (FVE), which can be performed in few minutes, is sensitive in mirroring neglect in everyday behaviour and whether it is more sensitive than conventional neuropsychological paper-pencil tests. In this retrospective, observational, multicentre study, we identified 78 patients in our database with subacute right-hemispheric stroke, with and without neglect in everyday behaviour, diagnosed by the CBS, who also performed FVE. 40 age-matched healthy participants served as controls. The sensitivity to detect neglect was compared between FVE (i.e., mean gaze position on the horizontal axis) and conventional neuropsychological paper-pencil tests, i.e., Random Shape Cancellation, Line Bisection, Two-Part Picture, Bells, Star Cancellation, Letter Cancellation, Sensitive Neglect, and Five-Point. FVE correctly identified neglect in 85%of patients, with an AUC-value of .922 in ROC-analysis. Conventional neuropsychological paper-pencil tests, considered alone or in combination, showed heterogeneous results, and identified neglect significantly less often (21.74%–68.75%). Moreover, there was a significant correlation between mean gaze position and CBS scores, providing evidence for the relationship between FVE and neglect in everyday behaviour. Furthermore, VLSM analyses suggested that the absence of a pathological rightward bias in FVE might depend on the integrity of the second branch of the right Superior Longitudinal Fascicle (SLF II), a white-matter tract connecting cortical areas critical for visual attention. Video-oculography during FVE has a high sensitivity and specificity to diagnose neglect after stroke and it is more sensitive than conventional neuropsychological paper-pencil tests. It can be performed in short time and has the potential to be used as a fast and accurate screening tool that allows the initiation of comprehensive neuropsychological diagnostics and therapy from early on.